BURNOUT AMONG EMPLOYED STUDENTS IN HIGHER EDUCATION: THE ROLES OF WORKLOAD AND ROLE CONFLICT - Khasanah, Nur (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2025)
This study examines the effects of workload and role conflict on burnout among employed students in higher education. An explanatory quantitative approach was adopted, involving students from the 2021 cohort of the Management and Accounting Study Programs at ITEBIS PGRI Dewantara Jombang who simultaneously undertook academic and employment responsibilities. Data were collected through a questionnaire survey and analyzed to determine the relationships among the variables under investigation. The findings indicate that both workload and role conflict significantly affect burnout among employed students. Notably, role conflict emerged as the more dominant predictor of burnout than workload. These findings underscore that burnout among employed students is driven not only by substantial task demands, but also by the incompatibility between academic obligations and work responsibilities. Accordingly, this study highlights the importance of institutional support and adaptive coping strategies in helping employed students manage the pressures associated with their dual roles more effectively